In vitro antibacterial activity of ethanol, methanol and water extracts of persimmon fruit (diospyros peregrine) against some multi-drug resistant human pathogens - Nur-Un-Nabi (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2010